Hubungan Kadar Magnesium Serum Dan Hba1c dengan Severitas Neuropati Diabetik - Andi Fadilah Yusran; Yuliarni Syafrita; Hendra Permana (Jurnal Ilmu Kedokteran, 2022)
Low magnesium levels are known to be associated with increased risk of diabetes mellitus and its complications. In addition, HbA1c levels are also known to have a correlation with further diabetes complications such as diabetic neuropathy. Diabetic neuropathy is the most common microvascular complication in diabetes mellitus, whose incidence is associated with disability and mortality rates in diabetic patients. This study aimed to assess the correlation between serum magnesium levels and HbA1c with the severity of diabetic neuropathy. This was a cross-sectional study. Severity of diabetic neuropathy is classified according to the Baba's Diabetic Neuropathy Classification (BDC). All subjects were examined for serum magnesium and HbA1C levels. This study consisted of 46 diabetes mellitus subjects, with 69.6% of the subjects suffering from diabetic neuropathy. The average magnesium level in this study was 1.87 mg/dl ± 0.245 and the median HbA1c level was 8.6 %. There was no significant correlation between serum magnesium levels and HbA1c with the incidence and severity of diabetic neuropathy (p>0.05). However, there was a significant negative correlation between magnesium levels and HbA1c levels in diabetic neuropathy patients.